Katechanas – ein lange verkannter mittelbyzantinischer Bei- bzw. Familienname - Seibt, Werner (Byzantinische Zeitschrift, 2017)
The surname of a Nikolaos πρωτοσπαθάριος καὶ πριμικήριος τῶν συνηγόρων resp. πρωτοσπαθάριος, θεσμογράφος καὶ πριμικήριος τῶν συνηγόρων on his lead seals from the time between 1040 and 1110 had been interpreted in the past with mistakes (Karichala, Katichael). Now we know three exemplars of each type and are able to correct to Κατιχανᾶς / Κατηχανᾶς. One more seal mentions an Ioannes Katechanas as β. κληρικός for a time between 1050 and 1110.The surname Katechanas is not documented elsewhere but has probably a Greek origin.null